Compensation those affected by technological development risks within the scope of medical works - حسن حيدر فليح; ارحيم عبد الله احمد (Journal of Legal Sciences, 2019)
compensation those affected by technological development risks within the scope of medical works. The unprecedented technological development the world witnesses nowadays has been providing brilliant medical service to the human being including examination, diagnosis and the treatment or follow up. However, such works hide behind potential risks threatening people’s lives and such risks my be discovered within the limits of now – how and technical knowledge prevailing the time of rendering the medical service. Also this the question is raised on how to keep up between the safety of the patients and such risks are being unknown by the provider and questioning them contradicts the justices. subsequently, can the patients (affected) acquire the compensation? The answer to such question is the basis of this research by divided two Requests. Reception the First Request compensation by the state and the second request compensation by national office for compensation.